2013
DOI: 10.1038/ncomms2499
|View full text |Cite
|
Sign up to set email alerts
|

Chemically programmed self-sorting of gelator networks

Abstract: Controlling the order and spatial distribution of self-assembly in multicomponent supramolecular systems could underpin exciting new functional materials, but it is extremely challenging. When a solution of different components self-assembles, the molecules can either coassemble, or self-sort, where a preference for like-like intermolecular interactions results in coexisting, homomolecular assemblies. A challenge is to produce generic and controlled 'one-pot' fabrication methods to form separate ordered assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
265
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(271 citation statements)
references
References 31 publications
6
265
0
Order By: Relevance
“…295 Shifts of the apparent pKa value is a well-known phenomenon for polymeric weak acids, self-assembled fatty acids and amphiphilic block copolymers, [298][299][300][301][302][303][304][305] and has been used by many research labs in order to fine-tune the pH-triggered self-assembly of linear 306,307 and aromatic peptide amphiphiles. 85,[308][309][310][311] A similar effect has been reported by Matile and coworkers in the b-sheet directed self-assembly of poctiphenyl b-barrel pores embedded in lipid bilayers. 312 Weakening of the basic character of protonated lysine and histidine side chains (apparent pK a of 7 and 4.5, respectively), as well as a weakening of the acidic character of aspartic acid side chains (apparent pK a of 6) was observed.…”
supporting
confidence: 57%
“…295 Shifts of the apparent pKa value is a well-known phenomenon for polymeric weak acids, self-assembled fatty acids and amphiphilic block copolymers, [298][299][300][301][302][303][304][305] and has been used by many research labs in order to fine-tune the pH-triggered self-assembly of linear 306,307 and aromatic peptide amphiphiles. 85,[308][309][310][311] A similar effect has been reported by Matile and coworkers in the b-sheet directed self-assembly of poctiphenyl b-barrel pores embedded in lipid bilayers. 312 Weakening of the basic character of protonated lysine and histidine side chains (apparent pK a of 7 and 4.5, respectively), as well as a weakening of the acidic character of aspartic acid side chains (apparent pK a of 6) was observed.…”
supporting
confidence: 57%
“…In the final gel, we used fiber X-ray diffraction to show that the data for the self-sorted gel are essentially an overlay of the expected data from the two individual gelators. 97 Here, we note that in many cases, self-sorting is difficult to prove by microscopy.…”
Section: Multicomponent Systemsmentioning
confidence: 99%
“…We have shown that this approach can be applied to a number of mixtures provided that the apparent pK a values are around a unit apart. 97,98 We have proven that self-sorting occurs by a number of techniques. Sequential assembly can be shown by solution-phase NMR.…”
Section: Multicomponent Systemsmentioning
confidence: 99%
See 2 more Smart Citations